1989
DOI: 10.1111/j.1399-6576.1989.tb02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects on the brain in connection with isoflurane‐induced hypotensive anaesthesia

Abstract: As a marker of brain cell injury, adenylate kinase (AK) was measured in cerebrospinal fluid (CSF) in 10 patients given anaesthesia with isoflurane-induced hypotension for corrective surgery of dentofacial deformities. Nine out of 10 patients displayed a marked increase in CSF-AK postoperatively compared with preoperative values. The postoperative mean value displayed a 400% increase compared to the corresponding preoperative value. This difference was statistically significant (P = 0.001). The rise in CSF-AK w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Confirmatory of a previous study the present work indicated an adverse metabolic effect on the brain in connection with isoflme-induced hypotension and orthognathic surgery (9). This was indicated by the release of a biochemical marker most probably originating from brain cells into the CSF in 24 of 37 patients (65%), and also indicated by a deterioration in psychometric tests in 4 patients out of 17 (24%) analysed.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Confirmatory of a previous study the present work indicated an adverse metabolic effect on the brain in connection with isoflme-induced hypotension and orthognathic surgery (9). This was indicated by the release of a biochemical marker most probably originating from brain cells into the CSF in 24 of 37 patients (65%), and also indicated by a deterioration in psychometric tests in 4 patients out of 17 (24%) analysed.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, under normal conditions the CSF-activity of this enzyme is zero or very low, <0.040 U/L (28). The previously observed enhanced efflux of AK into CSF in association with isoflurane-induced hypotensive anaesthesia was considered to be due to hypoxic brain cell injury secondary to hypotension (9). However, conflicting reports have been presented concerning the adverse effects of induced hypotensive anaesthesia on the brain (7,13,22,29).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this setting, modest hypotension or hypocapnia can accentuate brain hypoxic changes (Enlund et al, 1989;Hampson et al, 1990;Torella and McCollum, 2004). However, pathophysiological factors that may magnify this effect are unclear (Artru et al, 1998;Mehagnoul-Schipper et al, 2003).…”
Section: Introductionmentioning
confidence: 99%